Nate the Great - Sharmat, Marjorie Weinman; Simont, Marc (New York : Yearling, 2010)
Nate the Great solves the mystery of the missing picture. Includes related facts, jokes, recipes, and activities.
"Extra fun activities inside!"
RL: 2.0.
006-009.
Keywords: Mystery and detective stories